The critical fractional Schrödinger equation with a small superlinear term. (February 2019) - Zhang, Jian; Wang, Jichao; Ji, Yanju
Abstract: In this paper, we study the critical fractional Schrödinger equation with a small superlinear term. By using the Nehari manifold and the Lusternik–Schnirelmann category, we obtain two multiplicity results. Also, without the Ambrosetti–Rabinowitz condition or the monotonicity condition, we prove an existence result.